Arnaldo Antunes: por uma poética pós-concreta, hipermoderna - Prudêncio, Leonardo (2021)
Arnaldo Antunes'artistic work has been highlighted for its esthetic amplitude that comes with many ramifications in the artistic field. That puts him on the spot being one of the most creative poets in our days. When we learn about what Gilles Lipovetsky (2015) says about the hypermodernity, we can reach something in his theory that sees eye to eye with Arnaldo Antunes'posture and artistic production. To Enlarge the view about this specific subject we can cite some modern writers such as Paul Valéry (2018), Peter Bürguer (1993) and Harold Bloom (2003) and also some theorists that work with the contemporarity literature such as Augusto de Campos (2015); Leonardo Villa-Forte (2019), Carlos Felipe Moisés (2019) and Antonio Cicero (2017). Alessandra Santos'essay (2012) about the poet Arnaldo Antunes enlightens us to understand much more about his poetry and also helps us to find more information about the contemporarity poetry. This dissertation is structured in three chapters: the first one brings a historical situation of the Hypermodernity since the Modernists from 1922; the second chapter shows us the influences of the Concrete Poetry in Arnaldo Antunes'work; the third chapter shows us the hypermodernity in his work. We expect that this work about the hypermodernity in Arnaldo Antunes helps the researchers and enthusiasts of the paulistano and post-concretist poet and offers more knowledge about the literature in the beginning of the century